Estandarización de los procedimeintos para recepción de manera verde, secado, taller y encolaje de la Empesa Plantabal S.A. - Moran Reyes, Luis Enrique (2011)
The company was established in 1989, originally manufactured kits Balsa wood model cars in 2000 began with the manufacture of rigid and flexible panels. The location of the plant Maseca (Plantabal 1) is in the 10 ½ mile road to Daule. The management of the company in terms of quality it can be achieved by developing the Quality Management System, for which an analysis of the activities present in PLANTABAL. To identify the activities used checklists, inspections and surveys. The information collected was obtained in each of the activities of the production process. After data collection, these were unified for classification because of its importance. Standardization of procedures for receipt of green wood, drying, gluing workshop was developed under guidance issued by the Plant Manager and Quality Manager of the entire company.